Role of electrospun fibers coated on magnetoimpedance effect of Co-based ribbons - Zare, Mohammad; Jamilpanah, Loghman; Barough, Vahid; Sadeghi, Ali; Ghanaatshoar, Majid; Mohseni, Majid (Applied physics. A, Materials science & processing, 2024)
Aiming to enhance the performance of magnetic field sensors, this study focuses on depositing electrospun TiO 2 /PVA/CTAB composite nanofibers onto cobalt-based amorphous magnetic ribbons. The nanofibers have diameters of about 175–325 nm, where TiO 2 nanoparticles are uniformly dispersed in the fibers. The nanofiber-coated ribbons were analyzed using the giant magneto impedance (GMI) effect and we measured significant variation in the GMI ratio. The results demonstrate that the GMI response of the ribbon coated with nanofibers electrospun for 15 min exhibits a remarkable increase of 340% at a frequency of 10 MHz, compared to 290% for the uncoated ribbon. Nanofibers can be utilized for chemically or physically bonding additives to their surface, particularly for applications, where it is needed, for example, to detect biomaterials. Given their dielectric nature, these fibers hold potential for shielding against space charges and adhering to chemical components. They can be integrated with other materials to enhance the magnetoimpedance effect. Therefore, the application of non-magnetic electrospun nanofibers as coatings on magnetic sensors shows significant promise in augmenting their sensitivity and overall performance.